Very low surface recombination velocity in n-type c-Si using extrinsic field effect passivation - Bonilla Osorio, RS; Woodcock, F; Wilshaw, PR (AIP Publishing, 2014)
In this article, field-effect surface passivation is characterised as either intrinsic or extrinsic, depending on the origin of the charges present in passivation dielectric layers. The surface recombination velocity of float zone, 1 Ω cm, n-type silicon was reduced to 0.15cm/s, the lowest ever observed for a passivating double layer consisting of thermally grown silicon dioxide and plasma enhanced chemical vapour deposited silicon nitride. This result was obtained by enhancing the intrinsic chemical and field-effect passivation of the dielectric layers with uniform, extrinsic field-effect passivation induced by corona discharge. The position and stability of charges, both intrinsic and extrinsic, were characterised and their passivation effect was seen stable for two months with surface recombination velocity <2cm/s. Finally, the intrinsic and extrinsic components of passivation were analysed independently. Hydrogenation occurring during nitride deposition was seen to reduce the density of interfacial defect states from ∼5×10 10cm-2eV-1 to ∼5×109 cm-2eV-1, providing a decrease in surface recombination velocity by a factor of 2.5. The intrinsic charge in the dielectric double layer provided a decrease by a factor of 4, while the corona discharge extrinsic field-effect passivation provided a further decrease by a factor of 3. © 2014 AIP Publishing LLC.